Synergistic effect of Chitosan-Zinc Oxide Hybrid Nanoparticles on antibiofouling and water disinfection of mixed matrix polyethersulfone nanocomposite membranes. (1st November 2017) - Munnawar, Iqra; Iqbal, Sadia S.; Anwar, Muhammad N.; Batool, Mehwish; Tariq, Sheraz; Faitma, Nosheen; Khan, Asim L.; Khan, Asad U.; Nazar, Umair; Jamil, Tahir; Ahmad, Nasir M.
Graphical abstract: Highlights: Synthesis of antifouling Chitosan-Zinc Oxide Hybrid Nanoparticles (HNP). Fabrication of antifouling polymer membranes with incorporation of HNP. Increasing concentrations of HNP resulted in larger pores, flux and wettability. Synergistic antifouling effect of HNP were observed to disinfect water. Abstract: Antifouling polyethersulfone (PES) membranes for water disinfection were fabricated by incorporating varying concentrations of carbohydrate polymer chitosan and Zinc oxide hybrid nanoparticles (CS-ZnO HNPS). The CS-ZnO HNPS were prepared using chemical precipitation method and were characterized using SEM, XRD and FTIR. The membranes were then fabricated by incorporating nanoparticles of CS-ZnO HNPS with three different concentrations of 5%, 10% and 15% w/w in the casting solution of PES through phase inversion method. The influence of nano-sized CS-ZnO HNPS on the properties of PES was characterized to study morphology, contact angle, water retention, surface roughness and permeability flux. The membranes with the maximum concentrations of 15% HNPS resulted in larger mean pore sizes and lowest contact angle value as compare to the pristine PES membrane. The prepared membranes exhibited significant water permeability, hydrophilicity and prevention against microbial fouling. The prepared membranes were observed to have significant antibacterial as well as antifungal properties due to the synergistic effect of chitosan and ZnO against both bacteria of the type of S. Aureus, B. Cereus, E. coli, and fungi such as S. typhi, A. fumigatus and F. solani.